Forecasting Model with Box-Jenkins Method to Predict the Number of Tourists Visiting in Toraja - Didiharyono Didiharyono; Bakhtiar Bakhtiar (JEMMA (Journal of Economic, Management and Accounting), 2018)
This study aims to determine forecasting model with Box-Jenkins method and obtain results of data forecasting the number of tourists visiting in Toraja (Tanah Toraja and North Toraja regency) the future period. Research method used is applied research with quantitative data. Research procedures include identification of model, parameter estimation in model, verification and forecasting with using Minitab computer software. Based on the research obtained four models used in forecasting the number of tourists in Toraja the future period is ARIMA(1,1,1), ARIMA(2,1,1), ARIMA(1,2,1) and ARIMA(2,2,1). The correct criteria in selecting the best model is the model that has the smallest Mean Square (MS) value. In this case the time series model with the smallest MS value is ARIMA(2,2,1) that is 736062253. Thus, this model will used in forecasting is ARIMA(2,2,1) with equations . The forecasting results for January to December 2021 is 149985, 193099, 207559, 202903, 222426, 229294, 239108, 250921, 260701, 271895, 283037 and 294221.